THE CHARACTERISTICS OF RICE SOILS DERIVED FROM ALLUVIAL DEPOSITE AND THEIR MANAGEMENT - PRASETYO, BAMBANG HENDRO; SETYORINI, DIAH (Jurnal Sumberdaya Lahan, 2008)
Rice soils derived from alluvial deposite were spread almost in all Indonesian archipelago, due to the fact that the parent materials were resulted from sedimentation processes after erosion or weathering either in the upper course of river or the higher place, from the far or short distance. Generally the more distance of sediment material from the source of erosion or weathering, the more variation in the properties, and the closer of sediment material from the source of erosion or weathering, the more homogeny of the sediment material properties. The content and kind of weatherable mineral which were act as important source of nutrient inthe rice soils were influenced by parent materials. Among the parent materials, the sediment from intermediate to basic volcanic materials was the best supplier of nutrients. The most constrain in the alluvial rice soils are acidity and the nutrient content or source of nutrients. A balanced fertilizing based on soil testing is the best way to manage alluvial rice soils. For the area which is already had P and K nutrient status map at 1:50,000 scale, the fertilizing recommendation of primer macro nutrients could be refered to the map, while for the area that do not has a P and K nutrient status, the soil testing analyses should be done. Return straw to the ricefield is strongly recommended, because returned straw could be thrifty application of fertilizer, especially kalium (K).